Mechanisms underlying the monocyte-mediated antibody-dependent killing of Plasmodium falciparum asexual blood stages (The Rockefeller University Press, 1995)
The relevance of the antibody-dependent cellular inhibition (ADCI) of Plasmodium falciparum to clinical protection has been previously established by in vitro studies of material obtained during passive transfer of protection by immunoglobulin G in humans. We here report further in vitro investigations aimed at elucidating the mechanisms underlying this ADCI effect. Results obtained so far suggest that (a) merozoite uptake by monocytes (MN) as well as by polymorphonuclear cells has little influence on the course of parasitemia; (b) the ADCI effect is mediated by a soluble factor released by MN; (c) this or these factors are able to block the division of surrounding intraerythrocytic parasites at the one nucleus stage; (d) the critical triggering antigen(s) targeted by effective Abs would appear to be associated with the surface of merozoites, as opposed to that of infected red blood cells; (e) the MN receptor for Abs effective in ADCI is apparently Fc gamma RII, and not RI; (f) MN function is up- and down- regulated by interferon-gamma and interleukin 4, respectively; and (g) of several potential mediators released by MN, only tumor necrosis factor (TNF) proved of relevance. The involvement of TNF in defense may explain the recently described increased frequency of the TNF-2 high- expression promoter in individuals living in endemic regions despite its compromising role in severe malaria.